Management Skils In Primary Health Care Professionals: What To Be Developed To Optimize Resources And Improve Health? - Costa Dias, Ana Alexandra; Cunha, Conceição; Vitória, Andreia (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
New health needs introduce more complexity into health issues and, therefore, it requires a great deal more from caregivers, organizations and professionals, especially regarding professional qualifications, organizational models and their activities (Busse, Blumel, Kreinsen & Annette, 2010). Several authors (Barros, Machado & Simões, 2011; Busse et al., 2010; Dussault et al., 2014; Escoval et al., 2010, Hofmarcher, Oxley & Rusticelli, 2007) highlight the relevance that Primary Health Care (PHC) professionals can assume, arguing that these professionals should be able to provide a more complete and coherent response to new health needs, particularly with regard to the management of chronic disease. PHC professionals plays a central role, as they are primarily responsible for promoting health and preventing disease. Therefore, is the team of general and family medicine that is best positioned to guarantee the continuity in the provision of health care (Escoval et al., 2010). Family doctors are crucial in guiding the patient through the health system, assuming the role of patient navigator (Freeman, 2012), so, it is essential that they are motivated and qualified to coordinate activities and to ensure the interinstitutional articulation as well as the contact with the patient and / or their family. Thereby, PHC professionals are asked to be more than just health care providers, which implies mastering competencies beyond the technical ones of the health field. In this sense, it is important to evaluate the training needs of these professionals, given the new demands in the health care system (Hofmarcher et al., 2007). This subject has been quite studied in Portugal by Dussault et al. (2014), who set concrete proposals for Portugal, namely by optimizing the use of existing health professionals, giving them not only better working conditions, but also better organizational models and training plans so that these professionals are able to face the challenges that their jobs currently pose to them. Therefore, the need for a prospective and systemic view seems quite consensual and has been emphasized. In Portugal, this new paradigm emerged more clearly with the creation of the “Family Care Unit” (Decreto-Lei nº 298/2007) where health professionals assume greater autonomy in the functional and technical self-organization of these units. Thus, it is important to explore what kind of competences do they already have, specially concerning management skills, that can range from team leadership, through change management, partnership management and negotiation (Kumar, Kumar, Adhish & Reddy, 2015).In this sense, this work intends to contribute to this discussion, through the identification of a new training model project in Portugal at this level of care, namely the "Academia dos CSP”, presented as "a collaborative space for learning, citizenship, promoting the development and recognition of the knowledge, qualifications and practices of Human Resources and PHC Teams” (USF-AN, 2018). In fact, this project appears to be a successful training model, since it has been allowing to bridge the competences gap of the health professionals of the " Family Care Units" in the management area, because it has enabled them to acquire and develop skills in areas such as leadership, communication, governance, quality and information management. This project should be, in our point of view, better known, monitored and evaluated so that its contributions and limitations can be gauged, one can learn from experience so that, if successful, it can be replicated.